Synthesis of 4-(4-chlorophenyl)thiazole compounds: in silico and in vitro evaluations as leishmanicidal and trypanocidal agents - IRANILDO JOSÉ DA CRUZ FILHO; JAMERSON F. DE OLIVEIRA; ALINE CAROLINE S. SANTOS; VALÉRIA R.A. PEREIRA; MARIA CARMO A. DE LIMA (Anais da Academia Brasileira de Ciências, 2023)
Abstract Neglected tropical diseases are a diverse group of communicable pathologies that mainly prevail in tropical and subtropical regions. Thus, the objective of this work was to evaluate the biological potential of eight 4-(4-chlorophenyl)thiazole compounds. Tests were carried out in silico to evaluate the pharmacokinetic properties, the antioxidant, cytotoxic activities in animal cells and antiparasitic activities were evaluated against the different forms of Leishmania amazonensis and Trypanosoma cruzi in vitro. The in silico study showed that the evaluated compounds showed good oral availability. In a preliminary in vitro study, the compounds showed moderate to low antioxidant activity. Cytotoxicity assays show that the compounds showed moderate to low toxicity. In relation to leishmanicidal activity, the compounds presented IC50 values that ranged from 19.86 to 200 µM for the promastigote form, while for the amastigote forms, IC50 ranged from 101 to more than 200 µM. The compounds showed better results against the forms of T. cruzi with IC50 ranging from 1.67 to 100 µM for the trypomastigote form and 1.96 to values greater than 200 µM for the amastigote form. This study showed that thiazole compounds can be used as future antiparasitic agents.